Genetic Testing for Hereditary Gynaecological Cancer: An important and a New Avenue for developing Countries - Pokharel, Hanoon P (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To explore the scope of genetic testing for gynecological cancer in Nepal. Methods: Review of genetic testing methods and assessment of facilities and barriers within the country. Results: Country’s resources are still limited but the genetic testing cost is decreasing substantially. Gynecological service providers are increasing to provide services who can be the appropriate candidates to acquire training on genetic testing. Conclusions: Hereditary cancer diagnosis using stable buccal swab would be feasible with appropriate training.